Knowing Human Personality Based on Phisis Constitutional Typology According to Kretschmer and Sheldon’s Understanding - Zubaidah, Zubaidah; Harahap, Nurhasanah; Sari, Dwi Kurnia; Husna, Nurul; Husna, Nurul; Faradila, Septiana Amanda (Edumaspul: Jurnal Pendidikan, 2023)
Typology is knowledge that seeks to classify or group humans into certain types on the basis of certain factors, such as physical characteristics, psychics, dominant influences, cultural values, and so on. According to KBBI, typology is the science of character about the human part in groups according to their respective traits. Personality psychology is one of the branches of psychology that explains the human personality or all the behaviors and characteristics of individual habits that accumulate in him and it is used to react and can also adapt to all stimuli, both inside and outside of behavior and habits is a functional unity especially for a person. Kretschmer developed a human typology based on the physical constitution and psychic constitution based on the physical constitution, human types are further divided into 4 types, while based on the psychic constitution, humans are divided into two types. Kretschmer’s theory is one of the great works of the early 20th century. He was a German mental illness expert. Kretschmer built his topology on the basis of physical and psychological structures. Physical structure is divided into 4, namely the type of picnic, asthenic athletic and dysplastic. Personality is also defined and explained by different psychologists in various ways. William Herbert still has his own ideas about personality. He provides the theory that body type can be related to the personality of the person. more muscular body, more active and aggressive, thin or thin people with thin muscles are usually characterized as quiet or fragile.